PENGARUH METODE TARGHIB WA TARHIB TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS XI DI MA SYABILURRASYAD NWDI BARABALI TAHUN AJARAN 2025/2026 - Jalilah, Sofiatun; Sya’roni, Muh.; Hidayati, Nurul (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to determine whether there is an effect of the targhib wa tarhib method on student learning motivation in fiqh lessons in grade XI at MA Syabilurrasyad NWDI Barabali. The approach used in this study is a quantitative approach with a quantitative experimental research design. This study was conducted at MA Syabilurrasyad NWDI Barabali. The sample for this study consisted of 40 students in the 11th grade. The sample was selected using the purposive sampling method. The results of this study indicate that there is an effect of the targhib wa tarhib method on students' learning motivation in the fiqh subject for 11th grade students at MA Syabilurrasyad NWDI Barabali. This can be seen from the hypothesis test results, which show a significance value (p-value) of 0.000 (less than 0.05), so the alternative hypothesis is accepted and the null hypothesis is rejected. This means that there is a significant difference between the pretest and posttest scores of students' learning motivation after the application of the targhib wa tarhib method. The difference in the average scores between the pretest and posttest, which was 14.325 points, also indicates a significant increase in students' learning motivation. This is reinforced by the t-value of -25.540, which indicates a very significant difference between the results before and after the treatment, with a total of 40 respondents.